Magnetic resonance imaging for diagnosis of suspected neurogenic thoracic outlet syndrome-a systematic scoping review - Szaro, Pawel; Suresh, Rohan; Molokwu, Brian; Sibala, Dhiraj Raju; Mendiratta, Dhruv; Chu, Alice; McGrath, Aleksandra (Frontiers in Physiology, 2023)
Neurogenic Thoracic Outlet Syndrome (nTOS) is a rare pathology caused by dynamic conditions or compression of neurovascular structures in the thoracic outlet region. nTOS can be difficult to diagnose due to nonspecific symptoms and magnetic resonance imaging (MRI) techniques are increasingly used to aid the diagnosis and surgical planning. This scoping systematic review explores how MRI is used for diagnosing nTOS and summarizes details of published MRI protocols.A systematic screening of PubMed, Cochrane, Web of Science, and CINAHL databases using PRISMA-IPD guidelines was conducted in September 2022 to include full-text English papers on MRI and nTOS. Inclusion criteria involved studies describing MRI protocols for the diagnosis of TOS, with a focus on the imaging sequences and protocols.6289 papers were screened to include 28 papers containing details of MRI protocols. The details of MRI protocols in the analyzed articles were incomplete in all studies. Most authors used 1.5T systems and included T1 and T2-weighted sequences. Most studies applied fat suppression, mainly with STIR. Positioning of the arm differed between studies, including neutral, hyperabducted and abducted and externally rotated positions. This is a provisional file, not the final typeset articleOur review highlights a prevalent lack of detailed MRI protocol documentation for brachial plexus. Authors primarily rely on conventional 1.5T systems, employing standard T1 and T2-weighted sequences. The adoption of novel MRI sequences is notably lacking, and fat suppression techniques predominantly adhere to older methods as STIR. There is a clear imperative for authors to provide more comprehensive reporting of the MRI protocols utilized in their studies, ultimately enhancing comparability and clinical applicability. Establishing clear protocol reporting guidelines is crucial to allow for comparison between studies.